A sensitive and rapid ultra HPLC–MS/MS method for the simultaneous detection of clopidogrel and its derivatized active thiol metabolite in human plasma - Peer, Cody J.; Spencer, Shawn D.; VanDenBerg, Dustin A.H.; Pacanowski, Michael A.; Horenstein, Richard B.; Figg, William D. (Journal of chromatography. B, Analytical technologies in the biomedical and life sciences, 2012)
► We developed and validated a novel uHPLC–MS/MS assay for the simultaneous quantification of clopidogrel and its derivatized active metabolite. ► Clinically relevant calibration ranges for clopidogrel (0.01–50ng/mL) and active metabolite (0.1–150ng/m) were used. ► Successfully applied to clinical phase I study using 3 subjects. A sensitive, selective, and rapid ultra-high performance liquid chromatography–tandem mass spectrometry (uHPLC–MS/MS) was developed for the simultaneous quantification of clopidogrel (Plavix®) and its derivatized active metabolite (CAMD) in human plasma. Derivatization of the active metabolite in blood with 2-bromo-3′-methoxy acetophenone (MPB) immediately after collection ensured metabolite stability during sample handling and storage. Following addition of ticlopidine as an internal standard and simple protein precipitation, the analytes were separated on a Waters Acquity UPLC™ sub-2μm-C18 column via gradient elution before detection on a triple-quadrupole MS with multiple-reaction-monitoring via electrospray ionization. The method was validated across the clinically relevant concentration range of 0.01–50ng/mL for parent clopidogrel and 0.1–150ng/mL (r2=0.99) for CAMD, with a fast run time of 1.5min to support pharmacokinetic studies using 75, 150, or 300mg oral doses of clopidogrel. The analytical method measured concentrations of clopidogrel and CAMD with accuracy (%DEV) <±12% and precision (%CV) of <±6%. The method was successfully applied to measure the plasma concentrations of clopidogrel and CAMD in three subjects administered single oral doses of 75, 150, and 300mg clopidogrel. It was further demonstrated that the derivatizing agent (MPB) does not affect clopidogrel levels, thus from one aliquot of blood drawn clinically, this method can simultaneously quantify both clopidogrel and CAMD with sensitivity in the picogram per mL range.